Reanalyses of the sunspot observations of Fogelius and Siverus: two 'long-term' observers during the Maunder minimum. Issue 1 (7th October 2020) - Hayakawa, Hisashi; Iju, Tomoya; Uneme, Shoma; Besser, Bruno P; Kosaka, Shunsuke; Imada, Shinsuke
ABSTRACT: The solar activity during the Maunder minimum (MM; 1645–1715) has been considered significantly different from the one captured in modern observations, in terms of sunspot group number and sunspot positions, whereas its actual amplitudes and distributions are still under active discussions. In its core period (1650/1660–1700), Martin Fogelius and Heinrich Siverus have formed significant long-term series in the existing data bases. With numerous spotless days, they have been considered as the 13th and 7th most active observers before the end of the MM. In this study, we have analysed their original archival records, revised their data, have removed significant contaminations of the apparent 'spotless days' in the existing data bases, and cast caveats on the potential underestimation of the solar-cycle amplitude in the core MM. Still, they reported at best one sunspot group throughout their observational period and confirm the significantly suppressed solar cycles during the MM. This is also supported from the contemporary observations of Hook and Willoughby, analysed in this study. Based on their revised data, we have also derived positions of notable sunspot groups, which Siverus recorded in 1671 (≈N7.5° ± 2.5°), in comparison with those of Cassini's drawings (≈N10° ± 1°). Their coincidence in position and chronology in corrected dates indicates these sunspot groups were probably the same recurrent active region (AR) and its lifespan was significantly long (≥35 d) even during the MM.